If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + 3)(2x + 6) = 0 Reorder the terms: (3 + 7x)(2x + 6) = 0 Reorder the terms: (3 + 7x)(6 + 2x) = 0 Multiply (3 + 7x) * (6 + 2x) (3(6 + 2x) + 7x * (6 + 2x)) = 0 ((6 * 3 + 2x * 3) + 7x * (6 + 2x)) = 0 ((18 + 6x) + 7x * (6 + 2x)) = 0 (18 + 6x + (6 * 7x + 2x * 7x)) = 0 (18 + 6x + (42x + 14x2)) = 0 Combine like terms: 6x + 42x = 48x (18 + 48x + 14x2) = 0 Solving 18 + 48x + 14x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(9 + 24x + 7x2) = 0 Factor a trinomial. 2((3 + x)(3 + 7x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3Subproblem 2
Set the factor '(3 + 7x)' equal to zero and attempt to solve: Simplifying 3 + 7x = 0 Solving 3 + 7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 7x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 7x = 0 + -3 7x = 0 + -3 Combine like terms: 0 + -3 = -3 7x = -3 Divide each side by '7'. x = -0.4285714286 Simplifying x = -0.4285714286Solution
x = {-3, -0.4285714286}
| y=-x^2-10x+25 | | 10(b+4c)= | | 3x+34=9x-2 | | 1/(2sin(2x) | | 89-73=27y-31y | | 2x-(-4)=212 | | 2a+7=51 | | 2v-2=3v+15 | | 0.4n-1=35 | | 5x^2-7=49 | | 4b+36=9b+66 | | 4p-6=2p+4 | | (2x+4)+(3x^2-5x-3)=0 | | 0=-12p | | .5x^2-2x+3=0 | | -(4y+1)-(3y-8)=-1 | | 3x^2+11+5=0 | | 12=7/10g=44 | | 10(x+4)-2x=4x+2(2x+10)+20 | | 4e^3x=20 | | 4x^2+4x-17=0 | | 11(8r+3)2(9-6r)= | | 16n^2-161n=-5n^2-280 | | 9x^2-12x-8=0 | | -5x-30=3(x+4) | | 2y+2=9 | | X^2=2x+5 | | 675=4.50x | | 514=81.4+x | | (x-1)^2/3=4 | | 20x^3+60x^2+40= | | -10n+3(8+8n)=-6(x-4) |